EFEITOS FISIOLÓGICOS DA CONTAMINAÇÃO POR FERRO EM PHASEOLUS VULGARIS E ZEA MAYS - Silva, Rodolpho Henrique Waichert da (2022)
Understanding the toxic effects of iron on plant physiological processes appears as an important tool for promoting actions that aim to enhance agricultural production in areas under the influence of mining activities or whose environmental characterist